Current Status, Future Developments and Recent Patents on Photobioreactor Technology - G. Ramirez-Merida, Luis; Q. Zepka, Leila; Jacob-Lopes, Eduardo (Recent Patents on Engineering, 2015)
Carbon dioxide (CO2) has been regarded as one of the most important greenhouse gases. Microalgae are considered as a potential solution for the decrease of atmospheric CO2 levels. The design of photobioreactors capable of capturing CO2 for bioconversion bioproducts is the main issue for techno-economic success in the field of phototrophic biotechnology. There are two kinds of large scale photobioreactors: open and closed system. The open systems are raceway ponds and closed systems are the flat plate, vertical tubular and horizontal tubular. These photobioreactors have their own advantages and disadvantages. Improvements in the design and configuration of photobioreactors are widely evaluated, with a focus on the utilization of physical parameter suitable for scaling. However, some considerations must be taken into account such as the height/diameter (H/D) ratio, an appropriate value, which maintains control from the structural and physicochemical point of view, helping to provide sufficient volume of microalgae culture, efficient transfer of mass, a reaction volume where light input to the system is adequate, good rate of culture mixture and better utilization of land space. This review seeks to show some photobioreactor designs, some patents and their scale-up to be implemented in the CO2 sequestration and biomass production.
Keywords: photobioreactor